Commercial expectations and cooperation in symbiotic contracts a legal and empirical analysis - Soper, Charles Haward (Routledge, 2020)
"Exploring the role played by cooperation in the law and management of modern, complex contracts, this book contrasts an in-depth review of case law with a large-scale empirical study of the views of commercial actors responsible for the outcomes of these contracts. The possibility of aligning these expectations with the law is considered from the perspective that there is a general duty for parties to cooperate and ensure constructive engagement. The book examines how this might translate into constructive communication, professional governance, genuine attempts to settle issues, a right to fix defects, and a duty to take decisions in a fair and rational manner. Arguing that statutory adjudication should be extended to all commercial contracts and more ambitious of available remedies, including those for prevention and cost penalties, would help provide incentives for parties to cooperate more fully. The book will be of interest to academics in the fields of contract law and of contract management, as well as legal and commercial practitioners"--